THE ROLE OF WORKPLACE SPIRITUALITY IN REDUCING THE NEGATIVE IMPACT OF ORGANIZATIONAL CYNICISM ON JOB PERFORMANCE - Risgiyanti, Risgiyanti; Hidayah, Rini; T, Muhammad Fithrayudi (Universitas Brawijaya, Indonesia, 2020)
Organizational cynicism is now an important topic in the academic and business community, but the research relating to organizational cynicism is relatively neglected. Several studies that have examined the impact of organizational cynicism on job performance directly still show different results. This study strives to overcome this research gap by examining the impact of organizational cynicism on job performance by using variables of workplace spirituality as a moderating variable. The research data was taken from the supervisor and nurse from 7 private hospitals in the Pekalongan. The samples of this study were 176 respondents. The sampling technique was using convenience sampling. This research used a survey method with a quantitative approach and using the Partial Least Square (PLS) analysis tool with the help of WarpPLS 3.0. The results showed that organizational cynicism directly affects job performance. The results also show that spirituality in the workplace has a positive effect on job performance. Tests related to the effects of moderation suggest that workplace spirituality moderates the relationship of organizational cynicism on job performance. This study opens new avenues for research on organizational cynicism and carries implications for theory and practice.